2021
DOI: 10.3390/microorganisms9091893
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Nicotiana tabacum L. In Vitro Shoot Growth by Endophytic Bacillus cereus Group Bacteria

Abstract: In vitro plant tissue cultures face various unfavorable conditions, such as mechanical damage, osmotic shock, and phytohormone imbalance, which can be detrimental to culture viability, growth efficiency, and genetic stability. Recent studies have revealed a presence of diverse endophytic bacteria, suggesting that engineering of the endophytic microbiome of in vitro plant tissues has the potential to improve their acclimatization and growth. Therefore, the aim of this study was to identify cultivated tobacco (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Alternatively, a loss of mutualistic interaction with beneficial endophytic bacteria could contribute to reduced adaptation to in vitro conditions and inhibited shoot growth. Indeed, growth-promoting [ 5 , 9 ] stress-reducing activities [ 6 , 8 , 10 ] of bacteria on in vitro propagated plants have been reported previously. Our study revealed that antibiotic treatment significantly reduced the abundance of several families of order Rhizobiales as well as Caulobacteraceae and Sphingomonadaceae that involve many common environmental bacteria including beneficial plant-associated bacteria [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, a loss of mutualistic interaction with beneficial endophytic bacteria could contribute to reduced adaptation to in vitro conditions and inhibited shoot growth. Indeed, growth-promoting [ 5 , 9 ] stress-reducing activities [ 6 , 8 , 10 ] of bacteria on in vitro propagated plants have been reported previously. Our study revealed that antibiotic treatment significantly reduced the abundance of several families of order Rhizobiales as well as Caulobacteraceae and Sphingomonadaceae that involve many common environmental bacteria including beneficial plant-associated bacteria [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial DNA was isolated using the GeneJET Genomic DNA Purification kit (Thermo Fisher Scientific, Waltham, MA, USA). The 16S rRNA gene fragment was amplified using universal primers as described previously [ 10 ] and the sequence was queried at the NCBI BLAST server [ 88 ]. Isolate resistance to antibiotics was tested by cultivation on AIA medium supplemented with timentin (250 mg L −1 ), chloramphenicol (30 mg L −1 ), or rifampicin (25 mg L −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some bacterial endophytes maintain habitually concealed lifestyles or, due to limited bacterial growth-supporting media conditions, remain latent over extended periods of in vitro tissue cultivation. In fact, several studies showed a bene cial effect of endophytic bacteria on the growth of in vitro cultures of tomato [5], grapevine [6], sweet cherry [7], apple [8], purple cone ower [9] and tobacco [10]. However, the formation of bacterial colonies on culture media and bacterial overgrowth of plant tissues are common and manifest as infection by a variety of pathogenic species or the non-fastidious proliferation of commensal endophytic bacteria that can be triggered by changes in environmental conditions or plant host physiology [11][12][13].…”
Section: Introductionmentioning
confidence: 99%